Synthesis, Antibacterial study and ADME Evaluation of Novel Isonicotinoyl Hydrazide Derivative Containing 1,3,4-Oxadiazole Moiety - Mazen Mohammed Jwaid; Karima Fadhil Ali; Mayada Hadi Abd-alwahab (College of Pharmacy / Mustansiriyah University, 2022)
Novel derivative of isoniazid containing 1,3,4-oxadiazole pharmacophore has been synthesized. The chemical structure of the compound was characterized and confirmed by using FT-IR and 1H-NMR spectroscopy.   The desired compound was tested against gram-positive and gram-negative bacteria using agar well-diffusion technique for their ability as antibacterial agent and showed good antibacterial activity against gram-negative bacteria and gram-positive bacteria. In addition, ADME evaluations were performed using Swiss ADME to predict if the synthesized compound can be given orally, the bioavailability, topological polar surface area, and drug-likeness. The result showed that all tested compounds absorbed orally and fulfilled the Lipinski rule.